Shoreline changes in west african sandy coasts from Mauritania to Guinea Bissau: regional and local approaches by photo-interpretation, digital image processing and historical maps analysis - (:unkn) unknown (My University, 2010)
This PhD Thesis on shoreline changes in western african sandy coasts from Mauritania to Guinea Bissau is a contribution to the “Prospective review of the long-term coastal environment changes in western Africa”, scientific research component of the Regional Coastal and Marine Conservation Program for West Africa (PRCM). Its main objective was to highlight and measure erosion and accumulation processes occurred over several decades on the sandy shores from Mauritania to Guinea Bissau at regional and local scales. The comparison of the instantaneous waterline and the vegetation line positions extracted from multi temporal Landsat images by density slicing or classification with the ISODATA algorithms indicates a regional progradational trend of highly mobile coastal forms like sandy spits, small islands and beach barrier associated with the estuarine systems from Senegal to Guinea Bissau in spite of localized erosion cases. The local analysis focuses on four sites located along the Mauritanian and Senegalese shoreline (Nouakchott area, Ndiago – Saint-Louis, Bargny – Yene-sur-mer, Mbour – Pointe Sarène) and approximately stretching over 67 km. It is primarily based on digital processing and interpretation of aerial images in a GIS. Thereby the study of the spatial and temporal evolution of the position of selected shoreline indicators (high water line or upper beach limit) reveals that 47 km (70 %) of the studied coastline are eroding and only 20 km (30 %) are prograding.
Keywords: African Research